The bioenergetic “CK Clamp” technique detects substrate-specific changes in mitochondrial respiration and membrane potential during early VML injury pathology - McFaline-Figueroa, Jennifer; Hunda, Edward T.; Heo, Junwon; Winders, Elizabeth A.; Greising, Sarah M.; Call, Jarrod A. (Frontiers in Physiology, 2023)
Volumetric muscle loss (VML) injuries are characterized by nonrecoverable loss of tissue resulting in contractile and metabolic dysfunction. Characterization of metabolic dysfunction in VML-injured muscle has been interpreted from permeabilized myofiber respiration experiments involving saturating ADP levels and non-physiologic ATP:ADP concentration ratios. The extent to which this testing condition obscures the analysis of mitochondrial (dys)function after VML injury is unclear. An alternative approach is described that leverages the enzymatic reaction of creatine kinase and phosphocreatine to assess mitochondrial respiration and membrane potential at clamped physiologic ATP:ADP ratios, “CK Clamp”. The objective of this study was to validate the CK Clamp in VML-injured muscle and to detect differences that may exist between VML-injured and uninjured muscles at 1, 3, 5, 7, 10, and 14 days post-injury. VML-injured muscle maintains bioenergetic features of the CK Clamp approach, i.e., mitochondrial respiration rate (JO2) titters down and mitochondrial membrane potential is more polarized with increasing ATP:ADP ratios. Pyruvate/malate/succinate-supported JO2 was significantly less in VML-injured muscle at all timepoints compared to uninjured controls (-26 to -84%, p<0.001) and electron conductance was less at day 1 (-60%), 5 (-52%), 7 (-35%), 10 (-59%), and 14 (-41%) (p<0.001). Palmitoyl-carnitine/malate-supported JO2 and electron conductance were less affected following VML injury. VML-injury also corresponded with a more polarized mitochondrial membrane potential across the clamped ATP:ADP ratios at day 1 and 10 (pyruvate and palmitoyl-carnitine, respectively) (+5%, p<0.001). This study supports previous characterizations of metabolic dysfunction and validates the CK Clamp as a tool to investigate bioenergetics in traumatically-injured muscle.